The isolation and characterization of orbiviruses from ticks (ixodes uriae) - Spence, R (1984)
Ticks (Ixodes (Ceratixodes) uriae] were collected from two seabird colonies on the Isle of May in Scotland. Viruses were isolated from three tick pools, one from ticks collected during 1979 and two from ticks collected during 1981. The viruses replicated in suckling mouse brain, chick embryo fibroblasts, Vero and BHK-21 cells, but not in Xenopus cells. By virtue of their morphology in infected cells, physicochemical properties and reactions in complement fixation tests, they were identified as Kemerovo serogroup viruses belonging to the Great Island Complex (Orbivirus:Reoviridae). Ihe three isolates were distinguished from each other by plaque reduction neutralization tests. After three cycles of plaque purification, the replication of one isolate, Mill Door/79 virus, was examined in Vero and BHK-21 cells. The virus grew to maximum titres 8 to 9 hours post infection (p.i.); over 99% of the infectivity was cell-associated. Twelve virus-specified polypeptides, p141, p93, p69, p65, p53/51, p44, p37, p36, p30, p27, p21 and p20 were identified in infected Vero cell lysates by polyacrylamide gel electrophoresis (PAGE). Similar polypeptide profiles were observed in infected BHK-21 cell lysates. Attempts to purify the virus, by polyethylene glycol-6000 precipitation, resulted in the detection of p93, p69, p53/51, p37, p21 and p20 after PAGE, whereas only four, p93, p69, p53/51 and p37 were detected after attempts at purification using ether extractions. Results using pr~ase inhibitors and partial proteolysis indicated that three virus-specified polypeptides (p36, p30 and p27) may be cleavage products. All virus-specified polypeptides, with the exception of p30 and p20, were labelled in infected cell cultures with both [14c] mannose and [14c] glucosamine. [To continue reading the abstract please see the pdf]